A muon-spin relaxation (mu SR) study of the geometrically frustrated magnets Gd3Ga5O12 and ZnCr2O4 - Marshall, I; Blundell, S; Pratt, F; Husmann, A; Steer, C; Coldea, A; Hayes, W; Ward, R (2002)
We present the results of muon-spin-relaxation experiments for two materials which show geometric frustration. ZnCr22O4 has a spinel structure with S = 3/2 spins on a lattice of corner-sharing tetrahedra. Our experiments show that a local magnetic field which is quasi-static on the muon timescale develops below Tc = 12.5 K, a transition which has been associated with a three-dimensional analogue of the spin-Peierls transition. In contrast, Gd3Ga5O12 has a garnet structure with S = 7/2 spins arranged on interpenetrating triangular sublattices. In this material the muon data exhibit a temperature-dependent spin-relaxation rate indicative of slow spin fluctuations. We discuss these differing behaviours and relate them to the underlying physics in the two materials.